Super extra edge-connectivity in regular networks with edge faults. Issue 3 (4th May 2021) - Zhao, Shuang; Meng, Jixiang
ABSTRACT: Reliability evaluation of interconnection network is important to the design and maintenance of multiprocessor systems. And with the continuous increase in the size of networks, edge failure is inevitable. Motivated by this, we investigate the edge fault-tolerance of regular networks with respect to super extra edge-connectivity, denoted by ρ ( G ) . For a super extra edge-connected network G, ρ ( G ) is the maximum integer m for which G − S is still super extra edge-connected for any S ⊆ E ( G ) with | S | ≤ m . In this paper, we consider ρ ( G ) for two families of regular networks. As applications, several results of ρ ( G ) for some well-known networks are obtained.